INCIDENCE OF HEMATOLOGICAL MALIGNANCIES IN SICKLE CELL PATIENTS FROM AN INDIAN TERTIARY CARE TEACHING HOSPITAL - Chauhan, Sima; Swain, Santosh Kumar; Sahu, Mahesh Chandra (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Sickle cell disease (SCD) involves multiple systems and is manifested by variable degree of anemia, acute vaso-occlusive episodes, and chronic organ damage. Small case series have hinted at increased incidence of cancer among SCD patients, but no examination of population-based data in Odisha has been reported. Here, we have reported the association of hematological malignancies and SCD in our region. Methods: In this prospective study, we have documented all the demographic and clinical data of sickle cell patients during the past 3 years from June 2013 to May 2016. Simultaneously, the bone marrow (BM) aspiration and biopsy were carried out for all patients. This study was approved from the Institutional Ethics Committee. Results: A total number of 267 sickle cell patients were screened for malignancy by both BM aspiration and biopsy. Among them, 6 cases of malignancies were detected by both BM aspiration and biopsy method. Conclusion: Our study shows a association between SCD and hematological malignancies which could be due to treatment with hydroxyurea or accumulation of multiple genetic abnormalities due to a high degree of proliferative activity of marrow cells.